Elbow Biomechanics of Pitching: Does Age or Experience Make a Difference?. (September 2016) - Fehr, Shayne; Damrow, Derek; Kilian, Christopher; Lyon, Roger; Liu, Xue-Cheng
Background: Elbow pain and elbow injuries are common in youth baseball players. It is not clear whether pitching experience and/or age creates biomechanical differences at the elbow and whether these differences place an athlete at greater risk. Hypotheses: (1) Youth pitchers will have differing elbow kinematics with regard to flexion/extension, internal/external rotation, and pronation/supination when compared with nonbaseball athletes and (2) younger youth pitchers will have differing elbow kinematics when compared with older youth pitchers. Study Design: Case-control study. Level of Evidence: Level 4. Methods: Twenty-seven healthy male youths age 10 to 18 years were recruited and divided into an experience group (n = 18 pitchers) and a no experience group (n = 9 nonbaseball athletes). The experience group was subdivided by age into the younger experience subgroup (n = 10 pitchers) and the older experience subgroup (n = 8 pitchers). Biomechanics were recorded using an electromagnetic motion tracking system. Subjects from each group were averaged together, and a Mann-Whitney U test was utilized for statistical analysis. Results: The experience group had greater external rotation during late cocking (−47.8° vs 5.8°) and greater flexion during early cocking (112.8° vs 100.1°). The younger experience subgroup had greater range of motion with supination-pronation during early cocking (21.9° vs 11.2°) and late cocking (5.9° vs 2.0°). Conclusion: Youth athletes with pitching experience had an increase in maximal external rotation in late cocking and maximal flexion in early cocking, which suggests experience may be a factor to these parameters. The age of experienced baseball pitchers may be a factor due to differences observed with supination and pronation. Clinical Relevance: Learning to throw is a skill that leads to changes in elbow motion; however, these changes may be stable once athletes reach grade school age. Minimal differences were noted between the younger and older experience subgroups, which may underscore the importance of teaching proper mechanics at a young age.